Efficient evaluation of the Open QC task fMRI dataset - Etzel, Joset A. (Frontiers in Neuroimaging, 2023)
This article is an evaluation of the task dataset as part of the Demonstrating Quality Control (QC) Procedures in fMRI (FMRI Open QC Project) methodological research topic. The quality of both the task and fMRI aspects of the dataset are summarized in concise reports created with R, AFNI, and knitr. The reports and underlying tests are designed to highlight potential issues, are pdf files for easy archiving, and require relatively little experience to use and adapt. This article is accompanied by both the compiled reports and the source code and explanation necessary to use them.